Pengembangan Sistem Informasi Inventori Barang (Studi Kasus PT Satnetcom Kota Balikpapan) - Elvin Nasution; Djoko Pramono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT Satnetcom Balikpapan is a company that integrate, designs and develops a combination of communications, hardware and software for the mining, oil and gas industries. From the results of data collection that has been done by the author, it was found that information management of operational goods in the company's inventory is still done manually. Companies often find misinformation on inventory such as stock information on availability of goods, location of goods, and information related to item details. Frequently this misinformation causes delays in services provided by the company. In this study, we will build a website-based inventory information system with the Waterfall software development method. the results of functional testing with Black-box testing, the validity results are 100%, this shows that the system is running according to user expectations. And from the non-functional with compatibility testing test results found that information system of inventory can run very well on various computer web-browsers.